Organization in the Age of Hysteria - Howard Schwartz (EJP import test, 2018)
[caption id="attachment_2372" align="alignleft" width="1024"] "Luminous" by Stephen Mosblech[/caption] Summary: Civilization and organization require interplay between the spontaneous imaginary and the objective character of the symbolic, but these two are always in tension. Hysteria represents an attempt to end that tension through the destruction of the symbolic by the imaginary. A psychoanalytic theory of hysteria, based on the work of Lacan, Verhaeghe and Chasseguet-Smirgel is developed. The interdependence and antagonism of the imaginary and the symbolic are explored. Four aspects of this antagonism toward organization are discussed.
Keywords: civilization; Dark ages; hysteria; Imaginary; symbolic